2017
DOI: 10.3390/catal7020060
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic TiO2 Nanorod Spheres and Arrays Compatible with Flexible Applications

Abstract: Abstract:In the present study, titanium dioxide nanostructures were synthesized through microwave irradiation. In a typical microwave synthesis, nanorod spheres in the powder form were simultaneously produced with nanorod arrays grown on polyethylene terephthalate (PET) substrates. The syntheses were performed in water or ethanol with limited temperature at 80 • C and 200 • C. A simple and low-cost approach was used for the arrays growth, which involved a PET substrate with a zinc oxide seed layer deposited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 79 publications
4
69
0
Order By: Relevance
“…The network shape permits much more surface area for photocatalysis. These structures of NaOH-modified TiOF 2 have not been reported elsewhere. The Barrett-Joyner-Halenda (BJH) method was used to analyze the pore size distribution and pore volume and the surface area (S BET ) was calculated using the BET method.…”
Section: Phase Structures and Morphologymentioning
confidence: 89%
See 2 more Smart Citations
“…The network shape permits much more surface area for photocatalysis. These structures of NaOH-modified TiOF 2 have not been reported elsewhere. The Barrett-Joyner-Halenda (BJH) method was used to analyze the pore size distribution and pore volume and the surface area (S BET ) was calculated using the BET method.…”
Section: Phase Structures and Morphologymentioning
confidence: 89%
“…In the past, TiO 2 has been widely used as a photocatalyst in the photo-degradation of organic pollutants. However, it has a wide energy band gap (3.1-3.2 eV) which only permit its UV light response and can easily cause electron-hole recombination [1][2][3][4]. Thus, studies on changing morphology [1][2][3], modification [1,4,5], and other methods were conducted to decrease its band gap or inhibit its electron-hole recombination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, Huang et al [20] found that the modification of TiO 2 with Ag/AgCl obviously improved its photocatalytic activity. However, previous research has mainly focused on the fabrication of nano-sized Ag/AgCl/TiO 2 catalysts, such as nanoparticles [21,22], nanospheres [23], nanoarrays [20,24] and nanofibers [25]. These nano-sized catalysts are difficult to separate directly Figure 1a,c,e, the surface of TF is homogeneous and smooth, while the surface of CTF and S-CTF are rough.…”
Section: Introductionmentioning
confidence: 99%
“…He found that oxidation rate of 2-aminothiophenol using TiO2 NRA was found to be increased growth time. Daniela et al [14] was synthesized nanostructure of TiO2 nanorod array on PET substrate. The photocatalytic degradation rate under UV light was found to be 61% for the degradation of Rhodamine B dye.…”
mentioning
confidence: 99%